Molecular mechanism of Wilms' tumor (Wt1) (+/−KTS) variants promoting proliferation and migration of ovarian epithelial cells by bioinformatics analysis - Xiaomei Wang; Jingyu Zhao; Yixin Zhang; Yuxin Liu; Jinzheng Wang; Ruoxi Shi; Jinxiang Yuan; Kai Meng (BMC, 2023)
Abstract Epithelial ovarian cancer (EOC) is a gynecological disease with the highest mortality. With the lack of understanding of its pathogenesis, no accurate early diagnosis and screening method has been established for EOC. Studies revealed the multi-faceted function of Wilms' tumor (Wt1) genes in cancer, which may be related to the existence of multiple alternative splices. Our results show that Wt1 (+KTS) or Wt1 (−KTS) overexpression can significantly promote the proliferation and migration of human ovarian epithelial cells HOSEpiC, and Wt1 (+KTS) effects were more evident. To explore the Wt1 (+/−KTS) variant mechanism in HOSEpiC proliferation and migration and ovarian cancer (OC) occurrence and development, this study explored the differential regulation of Wt1 (+/−KTS) in HOSEpiC proliferation and migration by transcriptome sequencing. OC-related hub genes were screened by bioinformatics analysis to further explore the differential molecular mechanism of Wt1 (+/−KTS) in the occurrence of OC. Finally, we found that the regulation of Wt1 (+/−KTS) variants on the proliferation and migration of HOSEpiC may act through different genes and signaling pathways and screened out key genes and differentially regulated genes that regulate the malignant transformation of ovarian epithelial cells. The implementation of this study will provide new clues for the early diagnosis and precise treatment of OC.